A Longitudinal Examination of Socioemotional Learning in African American and Latino Boys Across the Transition From Pre‐K to Kindergarten. (29th July 2013) - Barbarin, Oscar
Abstract : Questions about socioemotional learning in boys of color (BOC) arise in light of the disproportionate rates of school adjustment difficulties BOC experience by adolescence. Socioemotional competence in BOC is assessed in terms of self‐regulation, interpersonal skills, and positive relationships with peers and teachers when they enter pre‐K. Changes in competence are tracked until the end of kindergarten. Teachers from randomly selected early childhood programs in 11 states rated children's socioemotional competence in the fall and spring of pre‐K. Children were followed through the end of kindergarten. Analyses compared Black ( n  =   278) and Latino ( n  =   347) boys to girls of color ( n  =   624) and White children ( n  =   1, 209) while controlling for family poverty. Pre‐K teachers rated a majority of BOC proficient on self‐regulation and peer relations. BOC did not differ from White boys on initial competence ratings or on development over time, although boys as a group were rated as less competent than girls. Although gender mattered in the initial assessment of socioemotional competence, gender was unrelated to change in competence over time. The longitudinal analyses showed a decline in teacher ratings of socioemotional competence from pre‐K to kindergarten. This decline was most likely attributable to the demands, structure, and didactic approaches common in kindergarten. Social competence did predict academic skills. Self‐regulation of emotions was the domain most consistently related to academic functioning. The vulnerability BOC experience during adolescence is not evident in the levels of social competence they demonstrate early in their lives at school.